2007
DOI: 10.1152/ajpregu.00806.2006
|View full text |Cite
|
Sign up to set email alerts
|

Greater uterine artery blood flow during pregnancy in multigenerational (Andean) than shorter-term (European) high-altitude residents

Abstract: Multigenerational (Andean) compared with shorter-term (European) high-altitude residents exhibit less hypoxia-associated reductions in birth weight. Because differences in arterial O(2) content are not responsible, we asked whether greater pregnancy-associated increases in uterine artery (UA) blood flow and O(2) delivery were involved. Serial studies were conducted in 42 Andean and 26 European residents of La Paz, Bolivia (3600 m) at weeks 20, 30, 36 of pregnancy and 4 mo postpartum using Doppler ultrasound. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 44 publications
12
78
2
1
Order By: Relevance
“…Hospital-based studies have documented that the risk of adverse perinatal outcomes is increased with extreme maternal Hcts (Moore et al, 2001a;Gonzales et al, 2009) (Fig.4). During pregnancy at high altitude, elevated Hct and the associated increase in blood viscosity contribute to an increased risk of stillbirth, preterm birth, and reduced birth weight, all of which appear to stem from a reduced uterine artery blood flow and, consequently, a reduced rate of O 2 delivery to the uteroplacental circulation (Moore et al, 1982;Moore et al, 2001a;Moore et al, 2001b;Zamudio et al, 1995;Wilson et al, 2007;Julian et al, 2008;Julian et al, 2009b). For this reason, acclimatized lowlanders at high altitude generally experience especially high rates of adverse pregnancy outcomes.…”
Section: Erythropoeitic Activitymentioning
confidence: 99%
“…Hospital-based studies have documented that the risk of adverse perinatal outcomes is increased with extreme maternal Hcts (Moore et al, 2001a;Gonzales et al, 2009) (Fig.4). During pregnancy at high altitude, elevated Hct and the associated increase in blood viscosity contribute to an increased risk of stillbirth, preterm birth, and reduced birth weight, all of which appear to stem from a reduced uterine artery blood flow and, consequently, a reduced rate of O 2 delivery to the uteroplacental circulation (Moore et al, 1982;Moore et al, 2001a;Moore et al, 2001b;Zamudio et al, 1995;Wilson et al, 2007;Julian et al, 2008;Julian et al, 2009b). For this reason, acclimatized lowlanders at high altitude generally experience especially high rates of adverse pregnancy outcomes.…”
Section: Erythropoeitic Activitymentioning
confidence: 99%
“…Previously we have shown that uterine artery (UA) diameter and blood flow are lower near term in women residing at high (3,100 m; 10,170 ft, Leadville) compared with low altitude (1,600 m; 5,280 ft, Denver) in Colorado (36). Greater maternal arterial oxygen content and/or UA blood flow, both of which are determinants of uteroplacental oxygen delivery, are associated with protection from SGA at high altitude (20,28,32,35,36). The frequency of preeclampsia, another condition in which UA blood flow is reduced, also increases with altitude and is responsible for approximately one-half of the altitude-associated reduction in birth weight, further demonstrating the importance of adequate UA blood flow to fetal growth at high altitude (13,15).…”
mentioning
confidence: 98%
“…The weight of the babies born to Tibetan residents at high altitude is more than that of those born to Han women living at the same altitude, which is associated with a higher uterine flow velocity and larger uterine arterial diameters [1]. The uterine arterial diameters in Andean pregnant women are also most doubling increased at high altitude whereas there are about half as much increase in European pregnant women [74]. As a result, Andean pregnant women have much higher uterine blood flows and birth weights of their babies than Europeans at high altitude.…”
Section: Uteroplacental Vascular Systemmentioning
confidence: 99%